The bone degenerative processes in senile fishes from Holocene Brazilian shell mounds. Issue 12 (14th July 2017) - Aguilera, O; Rocha, I; Lopes, M S; Lima, I; Lopes, R T; Machado, A S; Guimarães, R B; Crapez, M A C; Tenório, M C; Nepomuceno, A
Abstract: Zooarchaeological collections from shell mounds in Rio de Janeiro (2, 470–4, 632 cal BP) contain a high prevalence of swollen fish bones belonging to the Atlantic spadefish ( Chaetodipterus faber ), crevalle jack ( Caranx hippos ) and fat snook ( Centropomus parallelus ). Given the lack of knowledge of the bone degenerative process in senile fishes, this study analysed hyperostotic bone in zooarchaeological and modern specimens to obtain high‐resolution morphology and microstructure reconstruction. We used microCT as well as X‐ray diffraction to characterize the crystallographic changes associated with fish senility. Our results showed that trabecular microstructures in hyperostotic bones were consistent with estimated values of the per cent bone volume‐to‐total volume ratio (BV/TV) and were greater than 60% in cortical bone. Hyperostotic bones indicated a high radiograph density, and X‐ray diffractograms showed a decrease in hydroxyapatite [Ca10 (PO4 )6 (OH)2 ] and calcite (CaCO3 ) neocrystallization. These crystalline and density changes revealed an advanced stage of fish senile and indicate the vulnerability of ageing fish populations.